2017
DOI: 10.4103/ortho.ijortho_144_17
|View full text |Cite
|
Sign up to set email alerts
|

Current Concepts in Acetabular Positioning in Total Hip Arthroplasty

Abstract: Being one of the most successful surgeries in the history of medicine, the indications for total hip arthroplasty have widened and are increasingly being offered to younger and fitter patients. This has also led to high expectations for longevity and outcomes. Acetabular cup position has a significant impact on the results of hip arthroplasty as it affects dislocation, abductor muscle strength, gait, limb lengths, impingement, noise generation, range of motion (ROM), wear, loosening, and cup failure. The varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 73 publications
1
47
0
1
Order By: Relevance
“…Our study showed that a higher inclination angle of the cup is a significant risk factor for wear. The same results are seen in the literature, with inclination angles above 45 degrees[ 26 - 28 ]. Since the mean angle of CoPE in our group was above this angle, it supports that acetabular positioning is highly important to reduce wear of CoPE.…”
Section: Discussionsupporting
confidence: 90%
“…Our study showed that a higher inclination angle of the cup is a significant risk factor for wear. The same results are seen in the literature, with inclination angles above 45 degrees[ 26 - 28 ]. Since the mean angle of CoPE in our group was above this angle, it supports that acetabular positioning is highly important to reduce wear of CoPE.…”
Section: Discussionsupporting
confidence: 90%
“…The complete hip implant which is modeled with different cross-sections of stems, it is inserted into the femur bone. These implants are positioned into the bisected femur bone considering the patient’s femur and pelvic anatomy [28]. These hip implants along with femur are used for the static structural analysis in ANSYS R-19 to evaluate the best implant design out of the developed four different models.…”
Section: Methodsmentioning
confidence: 99%
“…Although ceramics have been described as biologically inert, sufficiently small enough particulates of zirconia, if released, may produce an immune reaction similar to those seen with polymers and metal debris [ 34 , 35 ]. Zirconia hypersensitivity and ALTR due to wear debris are multifactorial; however, we will describe what we believe to be the likely etiology in our case in the following paragraph [ 3 , 8 , 32 , 33 , 40 , [42] , [43] , [44] , [45] , [46] , [47] ].…”
Section: Discussionmentioning
confidence: 99%